PENGARUH PENGEMBANGAN KARIER TERHADAP KINERJA PEGAWAI PADA PT SUCOFINDO (PERSERO) JAKARTA - Vina Islami (Universitas Bina Sarana Informatika, 2017)
-The achievement of a goal the organization or company characterized by good performance of all employees. This makes the employee as an asset that is essential for an organization or company. Career development at PT Sucofindo (Persero) Jakarta is one of the influential program that aims to meet the needs of employees, in order to increase their performance in order to maintain employees as the most important asset. This study was conducted using a sample technique is saturated with respondents from 30 employees at the Human Capital division. Data obtained by observation, questionnaires, and literature were processed using SPSS V.17. Data processing results obtained by the correlation coefficient of 0.868 which has a very strong relationship between the career development of the performance. Based on the coefficient of determination obtained significant level of 0.000 <0.05. R Square of 0.754 which can be concluded that the career development has an influence on the performance while the rest of 0.246 influenced by other factors. The calculation of the regression coefficients obtained significant level of 0.000 where 0.000 <0.05 then H0 and H1 accepted. The value of a = 11.871, b = 0.724 value obtained regression formula Y = a + bx to Y = 11.871 + 0,724x. X = Career development, Y = Performance. So run career development has been good in the role that employee performance is increasing.Keywords: Career Developments, Employee’s Performance